Biophysical characterization of a swimmer with a unilateral arm amputation: a case study - Figueiredo, P.; Willig, R.; Alves, F.; Vilas-Boas, J. P.; Fernandes, R. J. (International Journal of Sports Physiology and Performance, 2014)
Purpose: To examine the effect of swimming speed (v) on the biomechanical and physiological responses of a trained front-crawl swimmer with a unilateral arm amputation. Methods: A 13-y-old girl with a unilateral arm amputation (level of the elbow) was tested for stroke length (SL, horizontal displacement cover with each stroke cycle), stroke frequency (SF, inverse of the time to complete each stroke cycle), adapted index of coordination (IdCadapt, lag time between propulsive phases), intracycle velocity variation (IVV, coefficient of variation of the instantaneous velocity-time data), active drag (D, hydrodynamic resistance), and energy cost (C, ratio of metabolic power to speed) during trials of increasing v. Results: Swimmer data showed a positive relationship between v and SF (R2 = 1, P < .001), IVV (R2 = .98, P = .002), D (R2 = .98, P < .001), and C (R2 = .95, P = .001) and a negative relationship with the SL (R2 = .99, P = .001). No relation was found between v and IdCadapt (R2 = .35, P = .22). A quadratic regression best fitted the relationship between v and general kinematical parameters (SL and SF); a cubic relationship fit the IVV best. The relationship between v and D was best expressed by a power regression, and the linear regression fit the C and IdCadapt best. Conclusions: The subject`s adaptation to increased v was different from able-bodied swimmers, mainly on interarm coordination, maintaining the lag time between propulsive phases, which influence the magnitude of the other parameters. These results might be useful to develop specific training and enhance swimming performance in swimmers with amputations.